Роль рослин у збереження водних ресурсів України - Дереведмедь, М. І.; Бабенко, Володимир Миколайович (ФОП Яроченко Я. В., 2024)
Based on theoretical methods and many years of practical research in various regions of Ukraine, confirmation was obtained of the leading role of various types of tree and grass vegetation in the formation of water resources in all regions of the country. The study is part of the creation and implementation of an appropriate water resources management system for the environmental safety of the natural waters of Ukraine.
Keywords: рослини; водні ресурси; водний баланс; природні поверхневі води; зелене насадження; органічне землеробство